InCIEC 2014 2015
DOI: 10.1007/978-981-287-290-6_27
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on the Issue of Delay in the Construction Industry

Abstract: Construction delay is a common problem in the construction industry. It is important to study this problem by investigating the overview of previous study on the issue of project delays and potential solutions to overcome it. Review of literatures shows the causes and necessary suggestions in project delays which is plaguing the construction industry in different nations. Various causes have been identified and suggestions have been poured out to minimize the problem as much as possible. Delay in projects is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Regardless of the reasons for the delay or who is at fault, project delays decrease the contract's value [1]. Therefore, the project manager is crucial in ensuring that the projects are finished within the budgeted time and cost, as stipulated in the contract because delays in construction projects create stress and worry for all the parties under the terms of the contract [4]. There are various types of delays in construction projects, which are based on the source or the affected parties for this delay.…”
Section: Delay In Construction Projectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of the reasons for the delay or who is at fault, project delays decrease the contract's value [1]. Therefore, the project manager is crucial in ensuring that the projects are finished within the budgeted time and cost, as stipulated in the contract because delays in construction projects create stress and worry for all the parties under the terms of the contract [4]. There are various types of delays in construction projects, which are based on the source or the affected parties for this delay.…”
Section: Delay In Construction Projectsmentioning
confidence: 99%
“…Another study in Saudi Arabia, Assaf et al [12] conducted research about construction project delays in different types of projects in the state. It was concluded that 70% of projects experience time overruns [4]. Table 1 summarizes the most causes of delay in construction projects that are related to different countries.…”
Section: Causes Of Delaymentioning
confidence: 99%
See 1 more Smart Citation
“…follow competitive bidding process for contractor selection (CS) which is mainly divided into two steps: (i) pre-qualification and (ii) bid evaluation. Around the world, the construction industry experiences delays that stop many ventures, and in some cases, it even causes complete surrender; alongside it is time and cost consuming, which accompanies different results like project failure, decrease of net profits and the deficiency of public certainty, especially on government-subsidised projects (Doraisamy et al 2015;Zailani et al 2016). Lo T. Y. et al (2006 in their research highlighted that construction delay factor, 'exceptional low bid,' was recognised as the third most huge reason for delay, which is practiced even today where L1 bidder is awarded the work amongst all the qualified bidders.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences are disputes and litigation between the parties, cost escalation, loss of profit, poor service quality, arbitrage, overrun of the deadline defined for executing the works or closing the project (AKOGBE;FENG;ZHOU, 2013;DOLAGE;PATHMARAJAH, 2015;GONZÁLEZ et al, 2014;GUNDUZ;OZDEMIR, 2015;KHAN;GUL, 2017;EL-RASAS, 2014;SWEIS, 2008;ULLAH et al, 2018). It is further observed that the delays in construction projects is a fact observed globally or on a large scale, affecting not only the industry itself, but the economy of nations in general; thus negatively impacting the success of the project due to changes in the original execution schedule and the previously established costs, quality criteria and management of safety conditions (CHAUHAN; SHAH; RAO, 2008;DORAISAMY;AKASAH;YUNUS, 2020;FARIDI;EL-SAYEGH, 2006;FLYVBJERG et al, 2002;MYDIN et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%